Assessing the role of FecB mutation in productivity of Indian sheep - Pardeshi, V. C.; Sainani, Mohini N.; Maddox, J. F.; Ghalsasi, P. M.; Nimbkar, C.; Gupta, V. S. (Current Science, 2005)
DNA samples from four Indian sheep breeds, viz. Garole, Deccani, Bannur and Madras Red were screened by PCR-RFLP to determine the presence of FecB mutation in these breeds. The Garole was the only breed, which carried the FecB mutation. The FecB mutation was introgressed from Garole sheep into Deccani sheep and Bannur sheep, and the performance of the crossbred sheep is being monitored in subsequent generations. Approximately half of the first backcross ewes (progeny of FecB heterozygote F1 rams) was found to carry one copy of FecB mutation, as expected. The FecB PCR-RFLP test was found to be fast, accurate and useful as a tool for making breeding decisions.
Keywords: FecB (Booroola) gene; Garole sheep; PCR-RFLP test; prolificacy

Assessment of Pongamia pinnata (L.) - a biodiesel producing tree species using ISSR markers - Sujatha, K.; Rajwade, A. V.; Gupta, V. S.; Hazra, Sulekha (Current Science, 2010)